Role of Ammonium Ions in Colloidal Silica Slurries for Ru CMP. (14th May 2019) - Wang, Ziyan; Zhou, Jianwei; Wang, Chenwei; Zhang, Jiajie; Wang, Qinwei; Wang, Ru
Abstract : The chemical mechanical polishing (CMP) of ruthenium (Ru) based barrier layer has been a pivotal process in the manufacture of a novel copper (Cu) interconnect structure. This paper mainly investigated the role of NH4 + in colloidal silica slurries for Ru CMP. The polishing results show that the Ru removal rate increases with the increasing concentration of NH4 + . The influence mechanism of NH4 + on removal rate of Ru was investigated by electrochemistry, scanning electron microscope (SEM) and zeta potential. It is revealed that the NH4 + can promote the surface corrosion rate of Ru by forming a water-soluble Ru-NH4 complex with Ru oxide, meanwhile can also result in the neutralization of the zeta potentials of both silica particles and the Ru surface, and thus can lead to the decrease of the electrostatic repulsive force and the increase of the mechanical abrasion intensity between silica particles and Ru surface. Further, the surface quality of the polished Ru wafer and slurry stability were evaluated, and the results show that the addition of an appropriate amount of NH4 + can achieve a low surface roughness of Ru and a high slurry stability.